Profiling the rural retail: An empirical study in the mountainous state of India. - Arora, Nitish; Kumar, Sarvesh (International Journal of Psychosocial Rehabilitation, 2020)
This paper is an empirical study to profile the rural retail stores situated in the hilly state of Himachal Pradesh, India. The study tries to create a profile of retail stores in terms of their physical structure and size, concerning the distance of the store from the National Highways. It also highlights the retail scenario and characteristics of retail stores situated on the National Highway and link roads of a mountainous state. This article explores the impact of location on the rural retail scenario. A mixed-methods research design has been used to conduct the study. Cross-tabulation chi-square tests and content analysis have been used to analyse both quantitative and qualitative sets of data. The study discovered that retail stores are made up of brick and concrete roofs and have no impact of location on them. The retailers situated near the National Highway have a higher income than the retailers situated on the link road markets. The one-store, multiple solutions strategy is followed in the rural markets. There are no weekly markets or haats present in the rural areas of Himachal Pradesh, which otherwise have a high presence across India.